Designing Home Security and Monitoring System Based on Field Programmable Gate Array - Assaf, Mansour H.; Mootoo, Ronald; Das, Sunil R.; Petriu, Emil M.; Groza, Voicu; Biswas, Satyendra N. (Technical review - IETE, 2014)
In the conventional design of home security systems, only the property is typically monitored, without taking into consideration the physical control aspects of the house itself. Besides, the term security is not strictly well defined in view of the fact that there is usually a time delay between the alarm system going on and actual arrival of the security personnel. This paper presents the development of a home security and monitoring system that is suitable where the traditional security systems that are mostly concerned about curbing burglary, gathering evidence against trespassing and so on fail. The design and implementation details of this new home control and security system which is based on field programmable gate array has been discussed in the subject paper. The user here can interact directly with the system through a web-based interface over the Internet, while home appliances like air conditioners, lights, door locks, and gates are controlled remotely through a user-friendly web page. An additional feature that enhances the security aspect of the system is its capability to monitor entry points such as doors and windows so that in the event of any breach, an alerting email message could be sent to the home owner instantly.